Entertainment Architecture: Constructing a framework for the creation of an emerging transmedia form - Konzal Woitek (Cultural Science)
The topic of this research is a novel entertainment form currently emerging from the youngest human communication technology, the Internet. This form, products based on it, and the conceptual framework describing it are all referred to as Entertainment Architecture (‘entarch,’ for short). Entarch is classified as Internet-native transmedia entertainment — it fully utilises the unique communicative characteristics of the Internet and is not based on just one medium. A number of entarch examples are explored through ‘immersive’ textual analysis — a new mode of textual analysis required for research into this kind of entertainment. As a secondary priority, entarch is related to the movie — which is chosen as an exemplary existing entertainment form finding itself in a radically uncertain formal, business, and industrial environment, and accordingly is struggling financially. Throughout, formal, business, and industrial consequences of the emergence of Entertainment Architecture are explored.